UMA VISÃO BACONIANA SOBRE PROBLEMAS AMBIENTAIS ATUAIS - dos Santos Cunha, Bianca (Prometheus - Journal of Philosophy., 2020)
The purpose of this article is to analyze two environmental tragedies that have recently occurred in Brazil: the rupture of the dam of the mining company Vale do Rio Doce in the municipality of Brumadinho in Minas Gerais and the use of pesticides in crops. Starting from the Baconian conception that the misuse of science can produce aberrations, especially from the analysis of the works The wisdom of the ancients (1609) and the New organum (1620), we intend to demonstrate how the same science that produced the necessary technology for the functioning The dam has decimated hundreds of people, devastating hectares of natural areas, dumping chemical waste that polluted rivers and devastated ecosystems. In addition, the unruly use of pesticides has increasingly compromised the Brazilian soil, contaminating springs and rivers, making society hostage to foods extremely infected with chemical substances, causing intoxication and putting the health of Brazilians at risk.